A study on bilateral trade: With special reference to India and Malaysia - Rengasamy, Dhanuskodi (SOCIAL TRANSFORMATION RESEARCH PLATFORM, UNIVERSITY OF SAINS MALAYSIA, EMAIL: osman@usm.my, 2012)
India and Malaysia share a very strong cultural and historical bonding. Economic and commercial relations are emerging as the mainstay of the bilateral relationship. Malaysia is the second largest trading partner for India within ASEAN, and India is the largest trading partner for Malaysia from among the countries of the south, excluding China. The study aimed to explore India's bilateral trade with Malaysia. In deep the study analyzed the India's export, import and balance of trade with Malaysia during the study period viz. 2006-07 to 2011-12. The study finds and concludes that the growth rate and trend, share percentage and growth percentage of India's export and import with Malaysia were positive and progress.